TINDAK TUTUR EKSPRESIF DALAM FILM SEJUTA SAYANG UNTUKNYA SUTRADARA HERWIN NOVIANTTO: Array - Karina, Meti Fitrotunnisa; Wakhyudi, Yukhsan (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2022)
This study aims to describe and analyze the expressive speech acts in the film â€œSejuta Sayang Untuknyaâ€ directed by Herwin Novianto. This study uses a ptagmatic approach The data of this research is in the form of dialogues quotes from characters in the film â€œSejuta Sayang Untuknyaâ€ director by Herwin Novianto, which is indicated to contain expressive speech act. The source of this research data is the film â€œSejuta Sayang Untuknyaâ€ director Herwin Novianto. The data collection technique used listening and note-talking techniques. The data analysis technique uses Miles and Huberman model analysis, which includes the process of data collection, data reduction, data presentation, and conclusion drawing/verification. The results of the study found as many 57 data of expressive speech acts, including; a) expressive praise, beauty, kidness; b) expressive gratitude, good deeds, honesty, and awards achieved; c) expressive blaming, regretting the actions that have been done, and ; d) expressive flattering, other people are embarrased; e) expressive apologize, for disappointing the speaker; f) expressive criticizing, disrespectful treatmen, increasingly complicated education; g) expressive complaining, feeling disappointed because of the actions taken.